2012
DOI: 10.5402/2012/361456
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study to Find Prevalence and Risk Factors for Childhood Asthma in Pune City, India

Abstract: We aimed to determine current prevalence of asthma and risk factors associated with it in Pune, India. Methods. This was a crosssectional school-population-based study in which parents of school children aged 6-7 and 13-14 were administered an ISAAC questionnaire and an additional set of questions that detected the presence of potential risk factors known to be associated with asthma during 2008-2009 academic years. Results. Prevalence of current asthma was 6.7% (7% amongst 6-7-year olds and 6.3% amongst 13-14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
7
21
0
Order By: Relevance
“…Dampness, fungus and moulds are rampant in these areas since it is a coastal area with high humidity; in our study 59.4 % of current wheezers lived in such surroundings. As per the study by Cheraghi M et al 4 , the presence of dampness (OR: 1.59, p<0.0001) at home was signifi cantly associated with asthma. Consumption of pasta/noodles, Chinese food and packed fried items (15.4% to 22%) was similar to the rates described in the study by Awasthi et.al.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Dampness, fungus and moulds are rampant in these areas since it is a coastal area with high humidity; in our study 59.4 % of current wheezers lived in such surroundings. As per the study by Cheraghi M et al 4 , the presence of dampness (OR: 1.59, p<0.0001) at home was signifi cantly associated with asthma. Consumption of pasta/noodles, Chinese food and packed fried items (15.4% to 22%) was similar to the rates described in the study by Awasthi et.al.…”
Section: Resultssupporting
confidence: 64%
“…Various studies have documented risk factors association with occurrence of asthma in school going children. 2,3,4,5 Asthma exacerbations by specifi c trigger factors are a well-known fact and how it affects their quality of life have been studied by Luskin AT et al 6 . Asthma exacerbations by asthma trigger factors have been documented by few studies 7,8,9,10,11 .…”
mentioning
confidence: 99%
“…Crude data could not be retrieved for four studies, and these were included in the adjusted meta-analysis only [21],[24],[25],[45]. Pooling of the 26 studies (1,500,916 individuals) for which unadjusted data were available showed a significant association between preterm birth and wheezing disorders (OR 1.71, 95% CI 1.57–1.87, p <0.001; Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Globally, asthma prevalence is growing by approximately 50% each decade, but is particularly pronounced in India and China. In India, recent reports have revealed a growth of 2.5% over 5 years in childhood asthma, highlighting future challenges for asthma care in the region …”
Section: Introductionmentioning
confidence: 99%
“…In India, recent reports have revealed a growth of 2.5% over 5 years in childhood asthma, highlighting future challenges for asthma care in the region. 4 Currently, there is limited data on the state of asthma management in the Asia-Pacific region, with most treatment practices being adopted from western countries. The rapid economic growth in Asia-Pacific countries, and the availability of effective medications and evidence-based treatment guidelines, has led to a rapid revolution in optimum asthma care in Asia-Pacific countries.…”
Section: Introductionmentioning
confidence: 99%